Resolusi Konflik Dalam Keluarga Terhadap Anak Yang Terlibat Dalam Hukum - Junaedi Junaedi; Abdullah Abdullah; Andi Lala (UNES Law Review, 2023)
This article explores the consequences of conflict resolution within the family sphere on children involved in the legal system. The discussion covers aspects such as sources of conflict, resolution strategies, and psychological impacts for children involved in legal situations. With an interdisciplinary approach, this article illustrates the complex relationship between family conflict and a child's journey through the legal system, specifically focusing on the long-term impact on their psychosocial well-being. The findings of this study provide valuable insights for legal practitioners, social workers, and relevant parties in handling children's cases involved in law, with the aim of enhancing a holistic approach and providing better support for these children.